Strategi Pengembangan Pindang Palembang Menggunakan Model Bisnis Canvas (MBC) Untuk Wisatawan - Melati Pratama (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2021)
Pindang Palembang is one of traditional culinary in South Sumatra which had uniqe special taste like sour, salty and sweet flavour. But, this culinary was not popular in tourist who come in Palembang. So, strategy of development for Pindang palembang need to be done. Development strategy was conducted based on BMC (Business Model Canvas) method by interview dan share quitioner with 24 hotels tourist. The initial identification showed that there were 24.39% foreign tourists who interest to Pindang palembang, the number of 45.45% taste was be value proposition, only 33.33% hotels gave offers about Pindang , the number of 30.91% unique was be customer relationships, the easy channel to reached was 85.37% online, the number of 66.67% hotels promoted Pindang palembang, 91.67% hotels had chef and 83.33% had website. By 7 elements, 78% cost structure low but it did’t have appreciations. BMC showed that, there were many factors affected Pindang development such as tourist attractions to Pindang , value of Pindang, mitra, promotion, media online, innovation and competence people who can developed Pindang to be interested taste.